Analisis Pengaruh Firm Size, Profitabilitas dan Kebijakan Dividen terhadap Market Capitalization dengan Good Corporate Governance sebagai Variabel Moderasi: (Studi Perusahaan yang Tercatat di Bursa Efek Indonesia Tahun 2021-2023) - Toliang, Ermina; Maulana, Arief Rio; Saputra, Edi (Jurnal Akuntansi Terapan dan Bisnis, 2024)
This study was conducted to determine the extent of the influence arising from firm size, profitability and dividend policy on market capitalization and whether good corporate governance can moderate the influence to be studied. The companies to be studied are companies listed on the Indonesia Stock Exchange with market capitalization that is always in the top 50 at the end of the year for 3 consecutive years. SPSS version 26 is used in this study as a tool in conducting the analysis. This study uses descriptive statistical tests, Multiple Linear Regression Analysis and moderate regression analysis. The results obtained in this study are that Firm Size and Dividend Policy have an effect on Market Capitalization, while profitability does not have an effect on Market Capitalization.